2001
DOI: 10.1002/bmc.130
|View full text |Cite
|
Sign up to set email alerts
|

Detection of two variant Vero toxin genes in Escherichia coli by capillary electrophoresis

Abstract: Three methods [capillary electrophoresis (CE)-allele-specific PCR, CE-single-strand conformation polymorphism (SSCP) and CE-cleavase fragment length polymorphism (CFLP)] were developed in order to effect rapid and specific analysis of the vero toxin (VT)1 and VT2 genes of O157. The allele-specific polymerase chain reaction (PCR) method, which utilized specific duplex PCR with specific primers for VT1 and VT2, showed that VT1 and VT2 consisted of 174 and 128 bp, respectively. Subsequent CE analysis was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Recently, Cipriani et al reported an application of CE‐AFLP to identify Fusarium oxysporum strain FT2, a fungal pathogen which is a potential mycoherbicide of a parasitic weed 80. In addition, when forward and reverse primers are labeled with different fluorescence dyes, terminal RFLP, which displays the end fragments, can be used as a modification of CE‐RFLP 61, 81, 82. Together with the characteristic patterns of restricted DNA fragments, exploration of the VNTR is another widely used genetic marker for identification of microorganisms.…”
Section: Nucleic‐acid‐based Detection Of Microorganisms By Cementioning
confidence: 99%
“…Recently, Cipriani et al reported an application of CE‐AFLP to identify Fusarium oxysporum strain FT2, a fungal pathogen which is a potential mycoherbicide of a parasitic weed 80. In addition, when forward and reverse primers are labeled with different fluorescence dyes, terminal RFLP, which displays the end fragments, can be used as a modification of CE‐RFLP 61, 81, 82. Together with the characteristic patterns of restricted DNA fragments, exploration of the VNTR is another widely used genetic marker for identification of microorganisms.…”
Section: Nucleic‐acid‐based Detection Of Microorganisms By Cementioning
confidence: 99%
“…However, these methods either lack sensitivity and precision, or cannot be multiplexed, reducing the high‐throughput capacity of these techniques 18. Other CE‐based SNP interrogation methods have recently emerged due to the versatility of this instrument 31–37. However, none of these CE methods combine the advantages of throughput, rapidity, large multiplex capacity and use of commercially available consumables.…”
Section: Resultsmentioning
confidence: 99%
“…There are two versions of the verotoxin (VT1 and VT2) with similar activity and its detection is important to prevent gastrointestinal syndrome. Advantages of combining CGE with three molecular techniques (allele specific PCR, SSCP and CFLP) to develop rapid and specific analysis of the VT1 and VT2 toxin genes of E. coli (O157:H7) have been studied [18]. Allele specific duplex PCR-CGE analysis showed separated peaks corresponding to 174 bp fragment VT1 and 128 bp fragment VT2 in 4 minutes (see…”
Section: Food-borne Pathogensmentioning
confidence: 99%
“…Separation conditions were 3% polyacrylamide, running temperature at 25ºC, voltage at 6.4 kV, capillary effective length: 7 cm, fluorescence dye: thiazole orange 0.1 µg/mL. Redrawn from ref[18].…”
mentioning
confidence: 99%